PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BAGIAN PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH (RSUD) MAJALAYA KABUPATEN BANDUNG - Winna Sarikusumaningtyas; Hendra Permadi (Juremi: Jurnal Riset Ekonomi, 2024)
Employee performance is an important factor in the organizational goals to be achieved. The good or bad performance of an employee in an organization will be determined by many factors including ability which is the result of knowledge and skills including personality attitudes which are influenced by education, training experience and interest and motivation as a result of the interaction of forces in physical conditions. work, social conditions of work and individual needs. This research was conducted in the Health Services Section of the Majalaya Regional General Hospital (RGH), the method used in this research was the descriptive analysis method, with a sample size of 60 people. The analysis method uses regression with SPSS software version 25. The results of this research support the hypothesis made, namely that training and work motivation have a positive and significant influence on employee performance. The results of the determination test show that the Training and Work Motivation variables can influence employee performance by 61.7%, while the remaining 38.3% is influenced by other variables not examined by the author. Based on the results of the research above, the Health Services Section of the Majalaya Regional General Hospital (RGH), Bandung District needs to improve its human resources in mastering knowledge and skills and increasing work motivation so that it will improve employee performance